PERANCANGAN SISTEM INFORMASI SKPI MENERAPKAN OUTCOME BASED EDUCATION BERBASIS WEB - Primaadi Airlangga; Mochammad Iqbal Syauqi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
The Outcome-Based Education (OBE) approach has been implemented in various developed countries to reduce the gap between education and the needs of the world of work. SKPI (Surat Keterangan Pendamping Ijazah) is an important supporting document that provides additional information regarding graduates' abilities and achievements. However, many universities still use a manual system based on Microsoft Excel, which is prone to data duplication and less efficient. This research develops a web-based SKPI information system using the Laravel 11 framework with a waterfall SDLC approach. The system includes stages of analysis, design, coding, testing, and maintenance and is equipped with security features such as data encryption to protect student information. It can manage and print descriptions of achievements, organizational activities, seminars, training, and student learning outcomes. Testing was conducted using black-box testing and user testing methods, showing that the system functions optimally and meets the needs. User feedback shows the system is efficient in supporting SKPI management